Information source and destination choice: mediation of perception of COVID-19 pandemic impacts and perception of destination - Le, Thi Mai; Bui, My-Trinh (Business: Theory and Practice, 2022)
The tourism industry has changed at its core in response to the emergence of economic vitality, climate change, and notably the recent COVID-19 outbreak. This study’s objectives are (1) to examine the factors affecting tourists’ destination choices, including their information sources, their perceptions of their destinations, and their perceptions of the COVID-19 pandemic’s impact and (2) to determine which of these factors play the most critical mediating role (i.e., perception of COVID-19 pandemic impact or perception of destination) in the relationship between information source and destination choice. Data from an online survey data of 645 respondents from Vietnam and MTurk were analyzed using SPSS version 22, Smart PLS 2.0 and Hayes Process 3.5. Our empirical findings suggest that (1) information source positively influences destination choice, (2) perception of the COVID-19 pandemic’s impact acts as a key mediator in the relationship between information sources and destination choices, and (3) perception of destination ranked first as the most vital factor in tourists’ destination choices. Our studies also discovered that the relationship from Information sources -> Perception of destination -> Destination choice is the strongest effect on travelers among the three indirect relationship. Our research will be of the greatest benefits to tourism stakeholders or tourism businesses as a foundation for further exploration into consumers’ behavior and attitudes toward destinations and help them to promote efficient emergencyresponse plans.